A simplified and robust protocol for immunoglobulin expression in Escherichia coli cell‐free protein synthesis systems. (18th April 2015) - Cai, Qi; Hanson, Jeffrey A.; Steiner, Alexander R.; Tran, Cuong; Masikat, Mary Rose; Chen, Rishard; Zawada, James F.; Sato, Aaron K.; Hallam, Trevor J.; Yin, Gang
<x xml:space="preserve">Abstract</x> Cell‐free protein synthesis (CFPS) systems allow for robust protein expression with easy manipulation of conditions to improve protein yield and folding. Recent technological developments have significantly increased the productivity and reduced the operating costs of CFPS systems, such that they can compete with conventional in vivo protein production platforms, while also offering new routes for the discovery and production of biotherapeutics. As cell‐free systems have evolved, productivity increases have commonly been obtained by addition of components to previously designed reaction mixtures without careful re‐examination of the essentiality of reagents from previous generations. Here we present a systematic sensitivity analysis of the components in a conventional Escherichia coli CFPS reaction mixture to evaluate their optimal concentrations for production of the immunoglobulin G trastuzumab. We identify eight changes to the system, which result in optimal expression of trastuzumab. We find that doubling the potassium glutamate concentration, while entirely eliminating pyruvate, coenzyme A, NAD, total tRNA, folinic acid, putrescine and ammonium glutamate, results in a highly productive cell‐free system with a 95% reduction in reagent costs (excluding cell‐extract, plasmid, and T7 RNA polymerase made in‐house). A larger panel of other proteins was also tested and all show equivalent or improved yields with our simplified system. Furthermore, we demonstrate that all of the reagents for CFPS can be combined in a single freeze‐thaw stable master mix to improve reliability and ease of use. These improvements are important for the application of the CFPS system in fields such as protein engineering, high‐throughput screening, and biotherapeutics. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:823–831, 2015